(untitled) (Fiep Bulletin - online, 2014)
This paper aims to identify the value of sports in modern society in the present 21st century, by way of the vision and influence of the pastors and workers that are members of the Assembly of God – Ouro Fino Ministry, Rio de Janeiro, Brazil. Initially, a bibliographical study was conducted, seeking to collect information and data about the theme under discussion. Next, an explorative survey was performed, with nine members of the Ministry, using a questionnaire prepared with open questions containing test words for Word Association. After obtaining this information, a more in-depth study can be developed on how to handle sports together with religion as a means of serving both interests (sports and religion), bringing harmony and benefits to those who are involved in such practices. It is considered possible to mix sports values with the beliefs of society and the target public – respecting both sides while taking advantage of the playful nature attributed to enjoyably practicing a sport – and, at the same time, use the Word of Christ, which often acts as an incentive. The Word penetrates human lives through listening, believing and practicing, living for Christ and being irreprehensible to sin, keeping oneself free of the imperfections of this world, seeking sanctification and awaiting Christ’s return. By way of the faith that nourishes our spirit and soul, we can also take care of our physical body, maintaining our health, enjoying the benefits of sports that offer us better physical fitness in our everyday lives (which are so hectic and stressful) and always distributing our time between work, rest and leisure.